UPAYA MENINGKATKAN DAYA TARIK KOTA SURAKARTA DI TINGKAT INTERNASIONAL MELALUI WARISAN BUDAYA - GPH. Dipokusumo, Langgeng Nugraha, Setyasih Harini & (Transformasi, 2016)
The cultural heritage is a relic of the past which was passed on from generation to generation ofmore protected, preserved, and maintained ownership. This study explain the efforts of theSurakarta local government enhances its appeal. Data collection techniques using observationand interviews. In the process of qualitative data analysis researchers used an interactivemodel. The results of the study point out that efforts to increase the attractiveness of the city ofSurakarta at the international level through: arts, ceremonies, events of an international nature,as well as other efforts to bolster the attractiveness of the city of Surakarta through the means ofcommunication that include international territories. The function of internationalcommunications in this study were: 1) Mendinamisasikan international relations by creating theslogan "Solo The Spirit Of Java", 2) Supporting efforts to achieve objectives of internationalrelations by joining the Organization World Heritage Cites (OWHC), 3) support the politicalIndonesian overseas through the middle power in the cultural aspect.Key words : International Communications, heritage culture, culture.